The Effect of Using Animated Videos in Introducing English Vocabulary in Group B Children - Laila, Maya Nur; Slamet, Sri (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This research aims to understand the impact of using animated videos in introducing English language learning to group B children at BA Aisyiyah Jetis 2 Sukoharjo in the 2023/2024 academic year. Methodology: The study employs a quantitative approach using a pre-experimental design, specifically a one-group pretest-posttest model. The sample consists of 25 children in group B. Data were collected through observation, and statistical analysis was conducted using a t-test with SPSS 15.0 for Windows. Results: The observation results show a significant improvement in English vocabulary recognition after the intervention. The average pretest score was 12.68, while the posttest average increased to 20.92. The t-test analysis yielded a calculated t-value of -16.449, which is less than the critical t-table value of -2.064. This indicates that the null hypothesis is rejected and the alternative hypothesis is accepted. Applications/Originality/Value: The findings suggest that animated videos are effective in enhancing English language acquisition among young learners. This research provides empirical evidence for educators to integrate multimedia tools, especially animated videos, into early childhood language instruction to increase engagement and learning outcomes.